Seat restraint use, previous driving history, and non-fatal injury: quantifying the risks. Issue 4 (1st October 1997) - Narayan, K M Venkat; Ruta, D; Beattie, T
Abstract : AIMS: To quantify the increased risk of non-fatal injury when children travel unrestrained in a car, and to identify other preventable risk factors. METHODS: Case-control study of 78 children presenting to an accident and emergency (A&E) department having sustained an injury while travelling in a car, and 97 children attending an A&E outpatient clinic with conditions unrelated to road traffic accidents. RESULTS: Seat restraint was associated with a 93% lower risk of child accident injury. A driver with points on the licence was over five times more likely to have had an accident resulting in child injury than a driver without points. Child accident injury was also associated with the driver's accident history. CONCLUSIONS: These data allow the effect of achieving new target levels of seat restraint use to be estimated. Strategies aimed at reducing the risk of further accident among drivers with a history of accident may have a beneficial impact on childhood accident injuries.